Online Shopping in Nepal: Preferences and Problems (Journal of Nepalese Business Studies, 2019)
The popularity of online shopping among Nepalese customers has increased with the cost-reduction of technology-based goods, the cost of internet services, and easy access to the internet. At the same time, the convenient modes of payments, and user-friendly, as well as, interactive shopping apps are further paving a pathway to unprecedented growth in the online shopping companies. The online shopping companies in Nepal have been seen following the Business to Consumer (B2C), Customer to Customer (C2C), or the ‘Facebook Store’ business model. The paper has taken 300 respondents, as a sample, who have at least twice shopping experiences, from a single online shopping company. The multiple-choice question, and open-end questions related to the preference, and problems faced were asked while going for online shopping in Nepal. In context to Nepal, time-saving, offers, easy ordering system and information available at the online shopping portal, were the main reasons for the shoppers, to prefer online shopping. The service quality provided by the online company, made the Nepalese customer, prefer online shopping. The quality of the product delivered to the customer was seen to be the major problem in Nepalese online shopping. The delivery of the wrong product was also seen one of the problems in online shopping in Nepal.